Realistic losses of rare species disproportionately impact higher trophic levels - Matthew E. S. Bracken; Natalie H. N. Low (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 461–467 Abstract Predicting the consequences of changes in biodiversity requires understanding both species’ susceptibility to extirpation and their functional roles in ecosystems. However, few studies have evaluated the effects of realistic, non‐random biodiversity losses, severely limiting the applicability of biodiversity research to conservation. Here, we removed sessile species from a rocky shore community in a way that deliberately mimicked natural patterns of species loss. We found that the rarest species in the system act from the bottom up to disproportionately impact the diversity and abundance of consumers. Realistic losses of rare species in a diverse assemblage of seaweeds and sessile invertebrates, collectively comprising